EVALUATION OF PHOSPHATE LEVELS AND MANAGEMENT STRATEGIES IN CHRONIC KIDNEY DISEASE-MINERAL AND BONE DISORDER PATIENTS IN A TERTIARY CARE HOSPITAL - SRINIVAS NAYAK SP; JITENDRA VAGHASIYA (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: This study aims to evaluate serum phosphate levels, their temporal variations, and the effectiveness of various treatment approaches in patients diagnosed with chronic kidney disease-mineral and bone disorder (CKD-MBD). Specific emphasis is placed on assessing the outcomes of current therapeutic strategies, including the use of phosphate binders, dietary interventions, and novel pharmacological agents. Methods: This study comprised 100 CKD-MBD patients in total. According to the Kidney Disease Improving Global Outcomes (KDIGO) standards, serum phosphate levels were classified, and variations over time were examined. The effect of phosphate binders, such as sevelamer and sucroferric oxyhydroxide, on serum phosphate levels was investigated to assess their impact on serum phosphate levels. Results: Out of the patients, 40% reported hyperphosphatemia and 60% retained the phosphate levels within the KDIGO-recommended range. The most prevalent phosphate range was 3.0–4.0 mg/dL (30%), which was followed by 2.0–3.0 mg/dL (27%). Of the patients, 30.55% saw a drop of 0.1–1.0 mg/dL, and 44.44% experienced a reduction of 1.0–2.0 mg/dL. The most common treatment strategy was a combination of sucroferric oxyhydroxide and sevelamer (40%), which was followed by sucroferric oxyhydroxide alone (35%), and sevelamer alone (25%). Conclusion: The outcomes indicate that a substantial proportion of CKD-MBD patients have the ability to keep their phosphate levels within the recommended range. Nonetheless, 40% of individuals exhibit persistent hyperphosphatemia, which emphasises the need for enhanced treatment techniques. Sucroferric oxyhydroxide and sevelamer found to be commonly used and had good control. Optimizing phosphate-lowering interventions, including dietary modifications and emerging therapeutic agents such as tenapanor, may help achieve better outcomes.